Impact of Orlistat-Induced Weight Loss on Diastolic Function and Heart Rate Variability in Severely Obese Subjects with Diabetes - Julie Martin; Carmen Paquette; Simon Marceau; Frédéric-Simon Hould; Stéfane Lebel; Serge Simard; Jean-Gaston Dumesnil; Paul Poirier (Journal of Obesity)
Objective. Determine the impact of Orlistat-induced weight loss on metabolic profile and cardiovascular function in severely obese patients with type 2 diabetes. Methods. Twenty-nine patients were randomized either to a nonplacebo control group or to a treatment group with Orlistat thrice a day. Metabolic profile, anthropometric parameters, heart rate variability indices, and echocardiographic variables were measured before and after a 12-week treatment period. Results. Treatment with Orlistat induced a modest but significant weight loss compared to controls (3.7 ± 3.0 versus 0.5 ± 2.2 kg, resp.; P=.003). There was significant decrease in fasting glycemia (7.9 ± 3.0 versus 6.7 ± 2.2 mmol/L; P=.03) and significant improvements in left ventricular diastolic function (P=.03) and in the sympathovagal balance (LF/HF ratio) (P=.04) in the Orlistat group. Conclusion. These results suggest that a modest weight loss improves fasting glycemia, left ventricular diastolic function, and sympathovagal balance in severely obese patients with type 2 diabetes.